IDENTITAS POLITIK KAUM BERSARUNG : RELASI THALIBAN DAN HUDA DALAM PROSES DAMAI ACEH - Mahmuddin, Mahmuddin (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
This study discussed the involvement and the ideology of politics of Taliban, HUDA in the Aceh peace process. Since the emergence of the Rabithah Thaliban Aceh movement (which later briefed as RTA) on April 7, 1999, was inseparable from social and political turmoil when the issues of referendum developed widely in the community. The power built by Thaliban and HUDA has been able to bring considerable influence in the event of political accumulation when the issues of referendum and independence became a requisite for the process of resolving the Aceh conflict. The peace process realized in Aceh in 2004 by involving international parties to the realization of the peace agreement in Helsinki. Thaliban and HUDA again voiced and gave political ideas in the arena of social and political development in Aceh. The struggle was intensified when the wishes of the people were not the same as the needs of the State.